Effect of Cymbopogon martini (Roxb.) Will.Watson essential oil on antioxidant activity, immune and intestinal barrier-related function, and gut microbiota in pigeons infected by Candida albicans - Huang, Ting; Zhang, Zheng-Yue; Qiu, Zhi-Lin; Li, Lin; Liu, Xian-Xi; Wang, Lei; Wang, Zi-Ying; Li, Zhi-Peng; Xiao, Geng-Sheng; Wang, Wei (Frontiers in Pharmacology, 2024)
Essential oils are potential alternatives to antibiotics for preventing Candida albicans (C. albicans) infection which is responsible for economic losses in the pigeon industry. Cymbopogon martini essential oil (EO) can inhibit pathogens, particularly fungal pathogens but its potential beneficial effects on C. albicans-infected pigeons remain unclear. Therefore, we investigated the impact of C. martini EO on antioxidant activity, immune response, intestinal barrier function, and intestinal microbiota in C. albicansinfected pigeons. The pigeons were divided into four groups as follows: (1) NC group: C. albicans uninfected/C. martini EO untreated group; (2) PC group: C. albicans infected/C. martini EO untreated group; (3) LPA group: C. albicans infected/1% C. martini EO treated group; and (4) HPA group: C. albicans infected/2% C. martini EO treated group. The pigeons were infected with C. albicans from day of age 35 to 41 and treated with C. martini EO from day of age 42 to 44, with samples collected on day of age 45 for analysis. The results demonstrated that C. martini EO prevented the reduction in the antioxidant enzymes SOD and GSH-Px causes by C. albicans challenge in pigeons. Furthermore, C. martini EO could decrease the relative expression of IL-1β, TGF-β, and IL-8 in the ileum, as well as IL-1β and IL-8 in the crop, while increasing the relative expression of Claudin-1 in the ileum and the crop and Occludin in the ileum in infected pigeons. Although the gut microbiota composition was not significantly affected by C. martini EO, 2% C. martini EO increased the abundance of Alistipes and Pedobacter. In conclusion, the application of 2% C. martini EO not only enhanced the level of antioxidant activity and the expression of genes related to intestinal barrier function but also inhibited inflammatory genes in C. albicans-infected pigeons and increased the abundance of gut bacteria that are resistant to C. albicans.